How to Integrate CYP2D6 Phenoconversion Into Clinical Pharmacogenetics: A Tutorial. Issue 3 (28th July 2021) - Cicali, Emily J.; Elchynski, Amanda L.; Cook, Kelsey J.; Houder, John T.; Thomas, Cameron D.; Smith, D. Max; Elsey, Amanda; Johnson, Julie A.; Cavallari, Larisa H.; Wiisanen, Kristin
Abstract : CYP2D6 genotype is increasingly being integrated into practice to guide prescribing of certain medications. The CYP2D6 drug metabolizing enzyme is susceptible to inhibition by concomitant drugs, which can lead to a clinical phenotype that is different from the genotype‐based phenotype, a process referred to as phenoconversion. Phenoconversion is highly prevalent but not widely integrated into practice because of either limited experience on how to integrate or lack of knowledge that it has occurred. We built a calculator tool to help clinicians integrate a standardized method of assessing CYP2D6 phenoconversion into practice. During tool‐building, we identified several clinical factors that need to be considered when implementing CYP2D6 phenoconversion into clinical practice. This tutorial shares the steps that the University of Florida Health Precision Medicine Program took to build the calculator tool and identified clinical factors to consider when implementing CYP2D6 phenoconversion in clinical practice.